Differential Characteristics of Professions from a Linguistic Perspective - Bokal, Ljudmila (Jezikoslovni zapiski, 2018)
This article examines the differential characteristics of professions based on linguistic criteria. It determines that, in addition to the terminological lexemes that are a relevant marker of a particular subject area, these also differ by linguistic criteria.